1968
DOI: 10.1017/s0043174500046804
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 2,4-D and Other Herbicides on Oxidative Phosphorylation in Mitochondria from Cabbage

Abstract: The effects of 22 herbicides on oxidative phosphorylation in mitochondria from cabbage (Brassica oleracea var. capitata L.) have been studied. Carbamates, phenoxyacids, 3,5-dimethyltetrahydro-l,3,5,2H-thiadiazine-2-thione (DMTT), N-1-napthylphthalamic acid (NPA), 2,3,6-trichlorobenzoic acid (2,3,6-TBA), 3-(p-chlorophenyl)-1,1-dimethylurea (monuron), and 2-chloro-2-N,N-diallylacetamide (CDAA) inhibited phosphorylation to a greater extent than oxygen uptake in cabbage mitochondria. The compounds 1,2-dihydropyrid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

1969
1969
1979
1979

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…Not only is ATP necessary for protein synthesis but it is also required for the RNA synthesis that precedes protein synthesis. Lotlikar et al (1968) found that chlorpropham effectively inhibited oxidative phosphorylation in cabbage mitochondria, inhibition being over 90% at 10"^ M. Dichlobenil at 1-45 x 10~* M inhibits ATP formation in isolated cucumber mitochondria by about 59% (Foy & Penner, 1965).…”
Section: Dichlobenil and Chlorprophammentioning
confidence: 96%
See 1 more Smart Citation
“…Not only is ATP necessary for protein synthesis but it is also required for the RNA synthesis that precedes protein synthesis. Lotlikar et al (1968) found that chlorpropham effectively inhibited oxidative phosphorylation in cabbage mitochondria, inhibition being over 90% at 10"^ M. Dichlobenil at 1-45 x 10~* M inhibits ATP formation in isolated cucumber mitochondria by about 59% (Foy & Penner, 1965).…”
Section: Dichlobenil and Chlorprophammentioning
confidence: 96%
“…Since one of the functions of GA in the germinating barley seed is to induce the de novo synthesis of a-amylase (Filner & Varner, 1967), it is not surprising that amylolytic activity in the barley endosperm test is reduced by dichlobenil and chlorpropham. Both herbicides have been shown to uncouple phosphorylation from electron transport (Lotlikar, Remmert & Freed, 1968;Foy & Penner, 1965), an activity that deprives growing plant tissues (such as a germinating seed) ofa readily-available supply of ATP. Not only is ATP necessary for protein synthesis but it is also required for the RNA synthesis that precedes protein synthesis.…”
Section: Dichlobenil and Chlorprophammentioning
confidence: 99%
“…In the intact plants of Elodea (Roth, 1958) and Seeale eereale (Ries et al, 1967) respiration was stimulated but in Convolvulus arvensis (Chodova and Zemanek, 1971) it was inhibited. With intact isolated mitochondria, Lotlikar, Remmert and Freed (1968) found a stimulation of respiration suggesting that simazine was acting as an uncoupler, although it had no effect on yeast mitochondria (Hachimori, Nosoh and Sone, 1968).…”
Section: Introductionmentioning
confidence: 94%
“…5 x 10"^ M), MCPA and MCPB were equally effective . Lotlikar (1960), using cabbage {Brassica oleracea L.) mitochondria, reported that 2,4-D and 4-(2,4-DB) inhibited phosphorylation to a greater degree than respiration and several authors have reported the activity of phenoxy-acid compounds as uncouplers or inhibitors of oxidation (see section on Effects on respiratory metabolism).…”
Section: Physiological Barriersmentioning
confidence: 99%
“…There is evidence that oxidative phosphorylation is influenced both by phenoxyacetic and phenoxybutyric compounds. Lotlikar (1960) reported that 2,4-D and 4-(2,4-DB) have a greater inhibitory eflect on phosphorylation than on respiration of cabbage mitochondria. Smith & Shennan (1966) found that 5 x 10"^ M MCPB completely inhibited endogenous respiration, whereas maximum inhibition by a similar concentration of MCPA was 52%.…”
Section: The Effects On Respiratory Metabolismmentioning
confidence: 99%